Ceramic crack repairing glaze and glazing repairing process
Through step-by-step grinding and segmented firing processes, combined with combined coupling agents and improved mullite and other materials, the problem of secondary cracking and inconsistent appearance after ceramic glaze repair is solved, and efficient ceramic repair and high-quality yield of finished ceramics are achieved.
Patent Information
- Application Number
- CN202510087584.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-20
AI Technical Summary
The existing ceramic glazing repair technology has the problem of secondary cracking after repair and the appearance of the repaired parts and the surrounding interface is inconsistent.
The step-by-step grinding method is used to change the angle between the grinding path and the crack and the grinding time, and use a combination of coupling agents and improved mullite materials to improve the adhesion and strength of the repair glaze through the segmented firing process and the regulation of the firing temperature, insulation time and cooling speed.
It effectively reduces the risk of secondary cracking of ceramics, improves the appearance consistency between the repairing area and the surrounding interface, and ensures that the ceramic repair area after firing is flat and free of cracks, and the yield rate reaches 99.7%.
Smart Images

Figure CN119874411A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic repair, in particular to a ceramic crack repair glaze and a glazing repair process. Background Art
[0002] Sanitary ceramics sometimes crack, fall off, and other unexpected situations during the production process, which require repair. Glaze repair is a technology for repairing damage to the surface of porcelain, but the existing repair methods have shortcomings such as insufficient adhesion between the repair glaze and the porcelain itself, and insufficient mechanical strength of the repair glaze after firing, which leads to a mismatch between the hardness of the repair area and the hardness of the porcelain itself, and the repair glaze is prone to falling off and secondary cracking. The repair technology requires no falling off and cracking, and requires no shrinkage after firing to ensure that the cracks can be completely flat and smooth after firing, without gaps, and have a smooth transition with the surrounding interface without color difference, so that the cracks in the ceramic products can be repaired perfectly. In the prior art, the height of the repair position of the repair glaze is often 0.1-0.25mm higher than the original glaze surface, and the repaired glaze surface is prone to crystallization, resulting in poor glaze repair effect. In summary, the existing ceramic glaze repair technology has the disadvantages of the risk of secondary cracking after repair and the inconsistency between the appearance of the repaired area and the surrounding interface.
[0003] Therefore, a ceramic crack repair glaze and a glazing repair process are proposed. Summary of the invention
[0004] The purpose of the present invention is to provide a ceramic crack repair glaze and a glazing repair process. The present invention overcomes the problems of easy secondary cracking and poor appearance consistency after repair in the existing ceramic repair technology. First, the semi-finished body with cracks is polished, and then the combined coupling agent is applied. After drying, the repair glaze A is sprayed for bisque firing, and then the repair glaze B is sprayed to cover the cracks, and finally fired to obtain the finished ceramic. By limiting the grinding time and the angle between the grinding path and the crack, changing the ratio and thickness of the combined coupling agent primer, adjusting the firing temperature, the heat preservation time and the cooling rate, and adding modified mullite to the repair glaze to reduce the risk of cracking; changing the addition amount of phosphate quartz, white garnet, wollastonite and modified mullite in the repair A glaze to reduce the glaze layer from falling off and cracking; changing the addition amount of polyvinyl alcohol, medium-temperature frit, tin oxide and titanium oxide in the repair B glaze to increase the viscosity of the glaze, reduce the risk of cracking, correct the color difference, and improve the appearance consistency.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A ceramic crack glazing repair process comprises the following steps:
[0007] S1 Use a soft brush to remove dust and debris from the cracks on the surface of the semi-finished ceramic body; First grinding: Use medium-grained sandpaper to grind the cracks along the direction of the cracks, remove protruding fragments, make the interfaces on both sides of the cracks smooth, then use a brush to remove the dust generated by grinding, and wipe it clean with a wet cloth; Second grinding: Use fine sandpaper to further grind and smooth along the direction of the cracks, so that the repaired area is flush with the surrounding surface; Third grinding: Use ultra-fine sandpaper to grind along the direction of the cracks, wipe it clean with a soft brush and a wet cloth, and dry it naturally to obtain a clean semi-finished ceramic body;
[0008] S2 sprays a 0.1-0.8mm thick combined coupling agent primer on the cracks of the cleaned semi-finished ceramic body, and after it dries, applies repairing glaze A on the cracks with a soft brush, and after it dries, polishes it with fine sandpaper until it is flush with the surrounding body, and removes dust to obtain a pre-treated semi-finished ceramic body;
[0009] S3 puts the pretreated semi-finished ceramic body into a kiln for firing. The first stage is bisque firing. The temperature is raised to 280°C at 2°C / min and kept at this temperature for 60 minutes. The temperature is then raised to 800°C and fired for 8 hours. The temperature is then lowered to room temperature at 2°C / min. The repair B glaze is evenly sprayed on the surface. After drying, a bisque fired semi-finished body is obtained. The second stage: the bisque fired semi-finished body is heated to 180°C at 2°C / min and kept at this temperature for 60 minutes. The temperature is then raised to a firing temperature of 1180-1260°C at 3°C / min and the temperature is kept at this temperature for 60-240 minutes. The third stage: the finished ceramic is obtained after the temperature is lowered to room temperature at 1-3.5°C / min.
[0010] Preferably, the grinding along the direction of the crack is reciprocating grinding with sandpaper in a grinding path parallel to the crack; the angle between the grinding path and the crack is 0-5°.
[0011] Preferably, the mesh number of medium-grained sandpaper is 120 mesh; the mesh number of fine sandpaper is 180 mesh; and the mesh number of superfine sandpaper is 320 mesh.
[0012] Preferably, the first grinding time is 3-10 min; the second grinding time is 15-20 min; and the third grinding time is 15-30 min.
[0013] Preferably, the combined coupling agent primer is a mixture obtained by mixing 3-aminopropyltriethoxysilane and 3-mercaptopropionic acid in a volume ratio of 1.12:0.78-1.43 and stirring at room temperature for 15 minutes.
[0014] Preferably, in the second stage S3, the sintering temperature is 1200-1220°C, and the holding time is 180-210 min; and in the third stage, the cooling rate is 2.5°C / min.
[0015] A ceramic crack repair glaze, including repair glaze A and repair glaze B;
[0016] In parts by weight, the raw materials for repairing glaze A are: 32 parts of halloysite, 15-18 parts of phosphotquartz, 10-13 parts of leucite, 5-8 parts of wollastonite, 6 parts of barium carbonate, 5 parts of zinc oxide, 8 parts of zirconium silicate and 15-20 parts of modified mullite;
[0017] In parts by weight, the raw materials for repairing glaze B are: 32 parts of halloysite, 18 parts of phosphate quartz, 13 parts of white garnet, 5 parts of zinc oxide, 5-12 parts of medium-temperature frit, 6 parts of barium carbonate, 2-8 parts of tin oxide, 2-5 parts of titanium oxide, 20 parts of modified mullite, and 0.2-0.5 parts of polyvinyl alcohol.
[0018] Preferably, the raw materials for repairing glaze A and repairing glaze B are respectively put into a ball mill, and 28% water of the total mass of the raw materials for repairing glaze A and repairing glaze B is respectively added, and after ball milling for 36 hours, the raw materials are sieved through 180 mesh to obtain repairing glaze A and repairing glaze B.
[0019] Preferably, mullite with a particle size of 25-50 μm is soaked in a boric acid solution with a mass concentration of 8% at room temperature for 60 minutes, and then filtered, washed and dried to obtain the modified mullite; the mass ratio of mullite to boric acid solution is 1:2.8.
[0020] Preferably, the raw materials for the repaired A glaze are, by weight, 32 parts of halloysite, 18 parts of quartz, 13 parts of leucite, 8 parts of wollastonite, 6 parts of barium carbonate, 5 parts of zinc oxide, 8 parts of zirconium silicate and 20 parts of modified mullite.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. Compared with fired ceramics, the ceramic semi-finished body has lower mechanical strength and is prone to deformation and cracking. More caution is required during the grinding stage when repairing cracks. The grinding path affects the direction of the grinding force. Grinding along the crack direction will reduce the force applied laterally to the crack. The present invention adopts a step-by-step grinding method to reduce the secondary cracking of the ceramic by changing the angle between the grinding path and the crack and the grinding time, thereby enhancing the bonding effect of the primer, the repair glaze and the body. The fired finished product rate is 99.2%, and there are no cracks or protrusions at the repair position after firing.
[0023] 2. The amino group in 3-aminopropyltriethoxysilane can combine with the hydroxyl group of the body and adhere tightly to the surface of the body at the crack; by introducing the thiol group in 3-mercaptopropionic acid, the chemical bonding force between the combined coupling agent primer and the ceramic body is enhanced, and the compatibility and bonding strength with the glaze are improved. By changing the volume ratio of 3-aminopropyltriethoxysilane and 3-mercaptopropionic acid, the body and the repair glaze are fully adhered. After firing, the glaze surface has good adhesion to the body, the repair glaze does not fall off, and the yield rate reaches 99.5%.
[0024] 3. The process of segmented firing is adopted. After applying the repair glaze A, the body is bisque fired to make the repair glaze A and the body fully bonded. After grinding and smoothing, the whole is sprayed with the repair glaze B, and then segmented high-temperature firing is performed. The segmented temperature rise firing makes the repair glaze A and the repair glaze B and the body tightly bonded, thereby enhancing the strength and thermal stability of the overall ceramic. The glaze surface of the fired ceramic repair area has a smooth transition with the surrounding area, without cracks, and the thermal stability is qualified. The yield rate reaches 99.7%.
[0025] 4. Add modified mullite to the repair glaze. Mullite has the characteristics of low shrinkage rate, which can reduce the risk of cracking and falling off caused by shrinkage of the glaze during firing. Mullite is modified by boric acid to chemically bond the repair glaze A with the amino and thiol groups in the combined coupling agent base material, reducing the phenomenon of falling off and cracking, improving the fluidity of the glaze and increasing the flatness. By adding modified mullite to the repair glaze A, changing the amount of phosphate, leucite, wollastonite, and modified mullite, the cracking rate is reduced and the glaze layer strength is improved. After firing, the ceramic repair glaze does not fall off, the surface is flat and crack-free, and the glaze layer strength is 250kPa.
[0026] 5. The raw materials for repairing glaze B are halloysite, quartz, leucite, barium carbonate, zinc oxide and modified mullite in the same amount as those for repairing material A, so as to reduce the difference in thermal expansion coefficients between the two glazes and reduce the risk of cracking; polyvinyl alcohol and medium-temperature frit are added to increase the adhesion between the glazes; tin oxide and titanium oxide are added to make the fired ceramic white, conceal the color difference between the cracks caused by repairing glaze A and the surrounding body, and make the finished product uniform in color; by changing the addition amount of medium-temperature frit, polyvinyl alcohol, tin oxide and titanium oxide, the viscosity of the glaze layer is 291Pa·s, and the whiteness value of the fired ceramic is 94.9%, the surface is smooth and the color is uniform. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Schematic diagram of the yield rate of Examples 18, 22-36 of the present invention. DETAILED DESCRIPTION
[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] See also Figure 1 The present invention provides a ceramic crack repair glaze and a glaze repair process, and the technical scheme is as follows:
[0030] The substance information involved in the present invention is as follows:
[0031] Boric acid CAS: 10043-35-3; Barium carbonate CAS: 513-77-9; Zinc oxide CAS: 1314-13-2; Zirconium silicate CAS: 10101-52-7; Lepidolite CAS: 1317-64-2; Tin oxide CAS: 18282-10-5; Titanium oxide CAS: 12137-20-1; Polyvinyl alcohol CAS: 9002-89-5; 3-Aminopropyltriethoxysilane CAS: 919-30-2; 3-Mercaptopropionic acid CAS: 107-96-0.
[0032] Example 1
[0033] Preparation of repair glaze A: soak mullite with a particle size of 25-50 μm in a boric acid solution with a mass concentration of 8% at room temperature for 60 minutes, filter, wash and dry to obtain modified mullite; the mass ratio of mullite to boric acid solution is 1:2.8; put 32 parts of halloysite, 15 parts of phosphate quartz, 10 parts of leucite, 5 parts of wollastonite, 6 parts of barium carbonate, 5 parts of zinc oxide, 8 parts of zirconium silicate and 15 parts of modified mullite into a ball mill, add 28% of the total mass of the raw materials of repair glaze A into water, ball mill for 36 hours and pass through a 180-mesh sieve to obtain repair glaze A;
[0034] Preparation of repair glaze B: Put 32 parts of halloysite, 18 parts of quartz, 13 parts of leucite, 3-11 parts of zinc oxide, 5 parts of medium-temperature frit, 6 parts of barium carbonate, 2 parts of tin oxide, 2 parts of titanium oxide, 15 parts of modified mullite, and 0.2 parts of polyvinyl alcohol into a ball mill, add 28% water of the total mass of the raw materials of repair B glaze, and after ball milling for 36 hours, pass through a 180-mesh sieve to obtain repair B glaze.
[0035] The glaze repair process steps are as follows:
[0036] S1 uses a soft brush to remove dust and debris from the cracks on the surface of the semi-finished ceramic body; first grinding: use 120 mesh medium-grained sandpaper to reciprocate and grind the crack for 3 minutes in a grinding path parallel to the crack, the angle between the grinding path and the crack is 0°, remove protruding fragments, make the interface on both sides of the crack flat, then use a brush to remove the dust generated by grinding, and wipe it clean with a wet cloth; second grinding: use 180 mesh fine sandpaper to reciprocate and grind for 15 minutes in a grinding path parallel to the crack, the angle between the grinding path and the crack is 0°, and further grind it smooth to make the repair area flush with the surrounding surface; third grinding: use 320 mesh ultra-fine sandpaper to reciprocate and grind for 15 minutes in a grinding path parallel to the crack, the angle between the grinding path and the crack is 0°, wipe it clean with a soft brush and a wet cloth, and dry it naturally to obtain a clean semi-finished ceramic body;
[0037] S2: 3-aminopropyltriethoxysilane and 3-mercaptopropionic acid are mixed in a volume ratio of 1.12:0.78 and stirred at room temperature for 15 minutes to obtain a combined coupling agent primer; a combined coupling agent primer with a thickness of 0.1 mm is sprayed on the cracks of the cleaned semi-finished ceramic body, and after it dries, a repairing glaze A is applied to the cracks with a soft brush, and after drying, it is polished with fine sandpaper until it is flush with the surrounding body, and dust is removed to obtain a pre-treated semi-finished ceramic body;
[0038] S3 puts the pretreated semi-finished ceramic body into a kiln for firing. The first stage is bisque firing, where the temperature is raised to 280°C at 2°C / min and kept at this temperature for 60 minutes, then raised to 800°C and fired for 8 hours, then cooled to room temperature at 2°C / min, and repaired by spraying glaze B evenly on its surface. After drying, a bisque fired semi-finished body is obtained. The second stage: the bisque fired semi-finished body is heated to 180°C at 2°C / min and kept at this temperature for 60 minutes, then raised to the firing temperature of 1180°C at 3°C / min and kept at this temperature for 60 minutes. The third stage: the finished ceramic is obtained after cooling to room temperature at 1°C / min.
[0039] Example 2-11
[0040] Referring to the preparation method and parameter conditions of Example 1, the specific differences are shown in Table 1.
[0041] Comparative Example 1
[0042] The preparation method and parameter conditions are the same as those of Example 7, except that the angle between the grinding path and the crack is 90°.
[0043] Comparative Example 2
[0044] The preparation method and parameter conditions are the same as those of Example 7, except that the polishing is not performed.
[0045] Table 1 Grinding parameters of Examples 1-11, Comparative Examples 1 and 2
[0046]
[0047] Example 12: Test on surface cracks, flatness and yield rate of finished ceramic products
[0048] The semi-finished green body with cracks of 1-2 cm was glazed and repaired using the glazing and repairing processes of Examples 1-11 and Comparative Examples 1 and 2. The surface cracks and flatness of the finished ceramics after firing were observed, and the yield was calculated. The results are shown in Table 2.
[0049] Table 2 Surface cracks, flatness and yield rate of finished ceramics of Examples 1-11 and Comparative Examples 1 and 2
[0050]
[0051]
[0052] Grinding can not only remove dirt, grease and old glue on the surface of the semi-finished body, but also remove burrs and uneven parts, ensure that the repair material is in direct contact with the surface of the body, so that the combined coupling agent primer and can better adhere to the surface of the semi-finished body to avoid the fall of the repair layer; by creating tiny grooves through grinding, the combined coupling agent primer and repair glaze can better "lock" into these grooves to improve the firmness of the repair. Use sandpaper of different grits to grind in stages, from large to small grits, which can save grinding time and avoid the problem of too thin body and surface depression of the finished product after firing caused by long-term grinding with high-grit sandpaper. When the angle between the grinding path and the crack is too large, lateral stress will be applied to the surface of the semi-finished body, making the body at the crack more fragile, and prone to secondary cracking in the subsequent firing process, reducing the yield rate. As shown in Table 1 and Table 2, in Examples 1-8, the final firing yield was improved by changing the time of the three grindings. In Example 7, the time of the first, second and third grindings was 6min, 18min and 25min respectively. The surface of the finished ceramic after firing was flat and crack-free, and the yield was 99.2%. In Examples 8-10, the angle between the grinding path and the crack was increased, and the yield was reduced to 98.0% when the angle was 5°. In Comparative Example 1, the angle between the grinding path and the crack was 90°. During grinding, a lateral force was applied to the body, resulting in obvious cracks on the surface of the fired ceramic and depressions. The yield was 87.1%; in Comparative Example 2, the semi-finished body was not ground, and the dust and dirt at the cracks affected the bonding of the primer and the repair glaze with the body, resulting in obvious cracks on the surface of the fired ceramic, and the repaired part was depressed compared to the surrounding plane. The yield was 90.5%.
[0053] Examples 13-20
[0054] Referring to the preparation method and parameter conditions of Example 7, the specific differences are shown in Table 3.
[0055] Comparative Example 3
[0056] The preparation method and parameter conditions are the same as those of Example 7, except that no combined coupling agent primer was used.
[0057] Example 21: Test on the glaze peeling off and yield rate of finished ceramic surface repair products
[0058] The semi-finished green body with a crack of 1-2 cm was glazed and repaired using the glazing repair process of Examples 7, 13-20 and Comparative Example 3. The shedding of the repair glaze on the surface of the finished ceramic after firing was observed, and the yield was calculated. The results are shown in Table 3.
[0059] Table 3: Falling off of repair glaze and yield rate of Examples 7, 13-20 and Comparative Example 3
[0060]
[0061] 3-Aminopropyltriethoxysilane is a silane coupling agent. It contains amino groups in its molecules and can combine with hydroxyl groups on the surface of the body to form silicon-oxygen bonds, so that the combined coupling agent primer adheres tightly to the surface of the body at the cracks, increasing the active sites on the surface of the body. The thiol group in 3-mercaptopropionic acid reacts with the hydroxyl groups on the surface of the ceramic body through hydrogen bonds or more stable covalent bonds to form chemical adsorption, increasing the bonding force between the body and the body, and enhancing the chemical bonding force between the combined coupling agent primer and the ceramic body. While the combined coupling agent primer is tightly bonded to the semi-finished body, it can also produce a cross-linking reaction with the repair glaze, forming a covalent bond with the glaze through the thiol group, thereby improving the cohesion and adhesion of the repair layer, improving the compatibility and bonding strength with the glaze, reducing the risk of the repair glaze falling off, and improving the yield rate. As shown in Table 3, in Examples 7, 13-16, the volume ratio of 3-aminopropyltriethoxysilane and 3-thiopropionic acid in the combined coupling agent primer was changed, and the repair glaze layer of the fired finished ceramic did not fall off, and the yield was improved; in Example 13, the volume ratio of 3-aminopropyltriethoxysilane and 3-thiopropionic acid was 1.12:0.90, and the repair glaze layer of the fired finished ceramic did not fall off, and the yield was 99.4%. The thickness of the combined coupling agent primer will also affect the repair effect of ceramic cracks. When the thickness is insufficient, the combined coupling agent has a weak bonding effect on the body and the glaze surface, and the coupling effect cannot be achieved; when the thickness is too large, the coupling agent completely covers the surface of the body, and the repair glaze is difficult to penetrate the coupling agent and contact the body, which reduces the connection strength between the repair glaze and the body. Bubbles or cavities are prone to appear during the firing process, reducing the mechanical strength of the finished product. In Examples 13, 17-20, the thickness of the combined coupling agent primer was changed, and the yield rate was improved; in Example 18, the thickness of the combined coupling agent primer was 0.6 mm, the repair glaze did not fall off, and the yield rate was improved to 99.5%. In Comparative Example 3, the combined coupling agent primer was not used, the connection strength between the repair glaze and the body was reduced, the fired finished ceramic repair glaze fell off, and the yield rate was reduced to 92.6%.
[0062] Examples 22-36
[0063] Referring to the preparation method and parameter conditions of Example 18, the specific differences are shown in Table 4.
[0064] Table 4 Firing parameters of Examples 18, 22-36
[0065]
[0066] Comparative Example 4
[0067] Referring to the preparation method and parameter conditions of the repair glaze in Example 1, the glaze repair process steps are as follows:
[0068] S1 uses a soft brush to remove dust and debris from the cracks on the surface of the semi-finished ceramic body; the first grinding: use 120 mesh medium-grained sandpaper to reciprocate and grind the crack for 6 minutes in a grinding path parallel to the crack, the angle between the grinding path and the crack is 0°, remove protruding fragments, make the interface on both sides of the crack flat, then use a brush to remove the dust generated by grinding, and wipe it clean with a wet cloth; the second grinding: use 180 mesh fine sandpaper to reciprocate and grind for 18 minutes in a grinding path parallel to the crack, the angle between the grinding path and the crack is 0°, and further grind it smooth to make the repair area flush with the surrounding surface; the third grinding: use 320 mesh ultra-fine sandpaper to reciprocate and grind for 25 minutes in a grinding path parallel to the crack, the angle between the grinding path and the crack is 0°, wipe it clean with a soft brush and a wet cloth, and dry it naturally to obtain a clean semi-finished ceramic body;
[0069] S2: 3-aminopropyltriethoxysilane and 3-mercaptopropionic acid are mixed in a volume ratio of 1.12:0.90 and stirred at room temperature for 15 minutes to obtain a combined coupling agent primer; a combined coupling agent primer with a thickness of 0.6 mm is sprayed on the cracks of the cleaned semi-finished ceramic body, and after it dries, glaze A is applied to the cracks with a soft brush for repair, and glaze B is evenly sprayed on the surface after drying, and fine sandpaper is used to grind it until it is flush with the surrounding body, and dust is removed to obtain a pre-treated semi-finished ceramic body;
[0070] S3 puts the pretreated semi-finished ceramic body into a kiln for firing, raises the temperature to 180°C at 2°C / min and keeps it at that temperature for 60 minutes, then raises the temperature to the firing temperature of 1180°C at 3°C / min, keeps it at that temperature for 60 minutes, then cools it to room temperature at 1°C / min to obtain the finished ceramic.
[0071] Example 37 Thermal stability, appearance effect and yield test
[0072] The ceramics fired in Examples 18, 22-36 and Comparative Example 4 were subjected to a water heat exchange at 180°C-20°C to test thermal stability. The ceramics that did not crack were qualified. The appearance of the repaired parts was observed and the yield was calculated. The results are shown in Tables 5 and Figure 1 shown.
[0073] Table 5 Thermal stability, appearance effect and yield rate of Examples 18, 22-36 and Comparative Example 4
[0074]
[0075] In the first stage, during the heating to 280℃ and keeping the temperature for 60min, the halloysite in the repair A glaze contains a certain amount of water and will be dehydrated at this stage; barium carbonate begins to decompose and releases carbon dioxide gas; lithium mica undergoes a dehydration reaction; the temperature is kept for 60min to allow the gas to fully overflow and eliminate bubbles; during the heating from 280℃ to 800℃ for 8h, phosphotidite, leucite, wollastonite and zirconium silicate undergo phase change and partial melting; modified mullite is a high-temperature stable phase with low shrinkage and its structure has not changed significantly; barium carbonate and zinc oxide are low-melting-point components that can melt at high temperatures, which helps to improve the fluidity of the repair A glaze. Lithops help to lower the melting point of the glaze and improve its solubility; at 800℃, the repair A glaze begins to melt, but it will not melt completely, which helps to evenly distribute the glaze on the body and improve the flatness of the glaze surface. The bisque firing in the first stage helps to expel the bubbles in the repair glaze A and improve the thermal stability of the ceramic. In comparative example 4, no bisque firing was performed, and the repair glaze A was directly sprayed with glaze B after drying, and then fired once after drying. The thermal stability of the finished ceramic was unqualified, and the repaired area was uneven, with cracks and small bubbles. During the second stage of firing, the halloysite, quartz, white garnet, and medium-temperature frit in the repair glaze B melted to provide a matrix for the glaze and form a uniform glaze surface, which helps the fluidity and covering ability of the glaze. Zinc oxide forms zinc silicate at high temperature to improve the thermal stability of the glaze. Barium carbonate will decompose and react with zirconium silicate in the glaze to form barium silicate, which increases the refractive index of the glaze and improves the glossiness. Tin oxide can reduce the expansion coefficient of the glaze and improve the thermal stability of the glaze. The modified mullite undergoes a phase change at high temperature to improve the thermal stability of the glaze. As shown in Tables 4, 5 and Figure 1 As shown, in Examples 18, 22-25, when the firing temperature is 1180-1260°C, the yield is 99.4%-99.6%, and the fired ceramics have qualified thermal stability, are flat, and have no cracks or bubbles. In Examples 22-23, the yield reaches 99.6% when the firing temperature is 1200-1220°C. Sufficient insulation time ensures that the chemical reaction in the glaze can be fully carried out, and the formation of stable compounds helps the glaze to melt evenly, reduce uneven glaze surface and particles, facilitate gas escape, reduce glaze bubbles, and long-term insulation helps to reduce internal stress caused by temperature gradients, reduce the risk of glaze cracking, and improve thermal stability. In Examples 29 and 30, the insulation time is 180min and 210min respectively, and the yield is 99.6%. During the ceramic firing process, a slow cooling rate helps to prevent the glaze and the body from cracking due to rapid temperature changes. In Examples 32-36, the cooling rate is 1-3.5°C / min. When the cooling rate reaches 3.5°C / min as in Example 36, the cooling rate is too fast, and the difference in expansion coefficient between the repaired glaze A and the repaired glaze B causes fine cracks to appear in the finished ceramic. In Example 34, the cooling rate is 2.5°C / min, and the repaired part of the finished ceramic is smooth without cracks or bubbles, and the yield rate is 99.7%.
[0076] Examples 38-45
[0077] Referring to the preparation method and parameter conditions of Example 34, the specific differences are shown in Table 6.
[0078] Table 6 Amount of raw material added for repairing glaze A in Examples 34, 38-45
[0079]
[0080]
[0081] Comparative Example 5
[0082] The preparation method and parameter conditions are the same as those of Example 45, except that the mullite is not modified with boric acid.
[0083] Comparative Example 6
[0084] The preparation method and parameter conditions are the same as those of Example 45, except that modified mullite is not added.
[0085] Example 46: Repair glaze peeling, finished ceramic appearance, and glaze layer strength test of repaired glaze A
[0086] The repair glaze A of Examples 34, 38-45 and Comparative Examples 5 and 6 was cast into a solid glaze rod in a plaster model, and the flexural strength of the dried glaze rod was measured to indicate the glaze layer strength of the repair glaze A. After firing, whether the repair glaze fell off and the appearance of the finished product were observed. The results are shown in Table 7.
[0087] Table 7: The peeling of the repair glaze of Examples 34, 38-45, Comparative Examples 5 and 6, the appearance effect and the glaze layer strength of the repaired glaze A
[0088]
[0089] Mullite has the characteristic of low shrinkage. When added as a raw material to the repair glaze A, it will reduce the risk of cracking and falling off caused by the shrinkage of the glaze during firing. The hydroxyl group on the surface of mullite reacts with one end of the silane molecule of the combined coupling agent primer, and the other end of the combined coupling agent combines with the hydroxyl group of the body, which improves the viscosity of the glaze layer of the repair glaze A and reduces the risk of the repair glaze falling off. Mullite is modified by boric acid to chemically bond the repair glaze A with the amino and thiol groups in the combined coupling agent primer, reducing the phenomenon of falling off and cracking. The mullite modified by boric acid makes the repair glaze A have better fluidity and wettability, which helps the repair glaze A to spread evenly on the surface of the primer material and improve the flatness. The borate ion can form a stable coordination bond with the amino group in the combined coupling agent primer, and at the same time form a thiol-boric acid adduct with the thiol group. This cross-linking effect can enhance the structure of the silane coupling agent network, thereby improving the adhesion between the repair glaze A and the primer. The introduction of borate can improve the heat resistance of the silane coupling agent layer. Under high temperature conditions, borate helps to maintain the stability of the coupling agent layer and prevents it from degrading and losing viscosity; borate interacts with the hydroxyl groups on the surface of mullite, improves the interfacial compatibility between the combined coupling agent and the repair glaze A, helps to improve the interfacial bonding strength, and reduces the risk of falling off and secondary cracking; as shown in Tables 6 and 7, in Comparative Example 5, the mullite was not modified with boric acid, the fired ceramic repair glaze fell off, there were protrusions and obvious cracks at the repaired area, and the glaze layer strength of the repaired glaze A was 202 kPa; in Comparative Example 6, no modified mullite was added, the fired ceramic repair glaze fell off, there were protrusions and obvious cracks at the repaired area, and the glaze layer strength of the repaired glaze A was 185 kPa. Phosphoquartz can lower the melting point of glazes, making them melt at lower temperatures, which helps to reduce energy consumption. Adding a proper amount of phosphoquartz can reduce thermal stress, prevent glaze cracking, and improve the gloss and transparency of the glaze. However, adding too much can cause the glaze melting point to be too low, the fluidity to be too high, and the glaze to have problems such as glaze flow or insufficient viscosity. Leucite can lower the melting temperature of glazes, increase the mechanical strength of glazes, and help to form a uniform glaze layer at a lower temperature, but adding too much can cause the glaze to be too rough, with reduced gloss, and even cracking. Wollastonite can improve the thermal stability of glazes, reduce thermal cracking, and adjust the viscosity of glazes. Adding a proper amount can help control the fluidity and spreadability of the glaze. Adding too much can cause the glaze to have excessive viscosity and poor fluidity, resulting in an uneven glaze surface. In Examples 34, 38-45, the addition amounts of quartz, leucite, wollastonite and modified mullite in the repair glaze A were adjusted, and the fired ceramic repair glazes did not fall off, and the surface was smooth and crack-free. The glaze layer strength of the repair glaze A was 233-250 kPa; in Example 45, 18 parts of quartz, 13 parts of leucite, 8 parts of wollastonite and 20 parts of modified mullite were added to the repair glaze A, and the glaze layer strength of the repair glaze A reached 250 kPa.
[0090] Examples 47-51
[0091] Referring to the preparation method and parameter conditions of Example 45, the specific differences are shown in Table 8.
[0092] Comparative Example 7
[0093] The preparation method and parameter conditions are the same as those of Example 45, except that tin oxide and titanium oxide are not added.
[0094] Table 8 Addition amount of raw materials for repairing B glaze in Examples 45, 47-53 and Comparative Example 7
[0095]
[0096]
[0097] Example 53: Test of glaze viscosity, finished ceramic appearance and whiteness value
[0098] The viscosity of the repaired B glaze of Examples 45, 47-53 and Comparative Example 7 was tested by an oscillating viscometer; according to the "QB-T1503-2011 Daily Ceramics Whiteness Determination Method", the whiteness values of the finished ceramics obtained in Examples 45, 47-53 and Comparative Example 7 were tested, and the appearance of the finished ceramics was observed. The results are shown in Table 9.
[0099] Table 9 Glaze viscosity, finished ceramic appearance and whiteness value of Examples 45, 47-53 and Comparative Example 7
[0100]
[0101] The addition amount of halloysite, quartz, leucite, modified mullite, zinc oxide and barium carbonate in the repair glaze B is consistent with that of the repair glaze A, so that the thermal expansion coefficient and shrinkage of the repair glaze B are similar to those of the repair glaze A, reducing the cracking phenomenon caused by firing. The addition amount of medium-temperature frit will affect the melting temperature, viscosity and fluidity of the glaze. The appropriate amount of frit can improve the gloss and mechanical strength of the glaze, but excessive frit may cause the glaze viscosity to be too high, affecting its fluidity and the quality of the final product; tin oxide can improve the opacity and whiteness of the glaze, and the addition amount of tin oxide will affect the viscosity and sintering behavior of the glaze. The appropriate amount of tin oxide can increase the gloss and whiteness of the glaze, but too much may make the glaze too viscous; titanium oxide can also improve the opacity and whiteness of the glaze, and its addition amount will also affect the viscosity and fluidity of the glaze. The appropriate amount of titanium oxide can make the glaze present good whiteness and covering power; polyvinyl alcohol is a binder and thickener, and its addition amount will affect the viscosity and fluidity of the glaze, thereby affecting the spraying effect of the glaze on the ceramic body. As shown in Tables 8 and 9, the addition amount of medium-temperature frit, tin oxide, titanium oxide and polyvinyl alcohol in Examples 45, 47-53 was increased, and the viscosity and whiteness value of the glaze layer also showed an upward trend; in Example 52, 12 parts of medium-temperature frit, 5 parts of tin oxide, 5 parts of titanium oxide and 0.3 parts of polyvinyl alcohol were added to obtain the repair B glaze, and the glaze layer viscosity of the repair B glaze was 291Pa·s, the whiteness value was 94.9%, and the fired ceramic surface was smooth and uniform in color. In Comparative Example 7, the repair B glaze was obtained without adding tin oxide and titanium oxide, the covering power of the glaze decreased, and the whiteness value was significantly reduced. The glaze layer viscosity of the repair B glaze was 271Pa·s, the whiteness value was 82.0%, the fired ceramic surface was smooth, and there was color difference at the repaired part.
[0102] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A ceramic crack glazing repair process, characterized in that The following steps are involved: S1: Use a soft brush to remove dust and debris from the cracks on the surface of the semi-finished ceramic body; first grinding: use medium-grained sandpaper to grind the crack along the direction of the crack, remove protruding fragments, make the interface on both sides of the crack flat, then use a brush to remove the dust generated by grinding, and wipe it clean with a wet cloth; second grinding: use fine sandpaper to further grind and smooth along the direction of the crack, so that the repair area is flush with the surrounding surface; third grinding: use ultra-fine sandpaper to grind along the direction of the crack, wipe it clean and dry it naturally to obtain a clean semi-finished ceramic body; S2: spraying a 0.1-0.8 mm thick combined coupling agent primer on the cracks of the cleaned semi-finished ceramic body, applying a ceramic crack repair glaze A glaze on the cracks after drying, and grinding with the fine sandpaper until it is flush with the surrounding body after drying, and removing dust to obtain a pre-treated semi-finished ceramic body; S3 puts the pretreated semi-finished ceramic body into a kiln for firing. The first stage is bisque firing. The temperature is raised to 280°C at 2°C / min and kept at this temperature for 60 minutes. The temperature is then raised to 800°C and fired for 8 hours. The temperature is then lowered to room temperature at 2°C / min. The repair B glaze of the ceramic crack repair glaze is evenly sprayed on the surface. After drying, a bisque fired semi-finished body is obtained. The second stage: the bisque fired semi-finished body is heated to 180°C at 2°C / min and kept at this temperature for 60 minutes. The temperature is then raised to a firing temperature of 1180-1260°C at 3°C / min, and the holding time is 60-240 minutes. The third stage: the finished ceramic is obtained after the temperature is lowered to room temperature at 1-3.5°C / min.
2. A ceramic crack glazing repair process according to claim 1, characterized in that: The grinding path along the direction of the crack is reciprocating grinding along a grinding path parallel to the crack; the angle between the grinding path and the crack is 0-5°.
3. The ceramic crack glazing repair process according to claim 1, characterized in that: The mesh number of the medium-grained sandpaper is 120 meshes; the mesh number of the fine sandpaper is 180 meshes; and the mesh number of the superfine sandpaper is 320 meshes.
4. The ceramic crack glazing repair process according to claim 1, characterized in that: The first grinding time is 3-10 minutes; the second grinding time is 15-20 minutes; and the third grinding time is 15-30 minutes.
5. The ceramic crack glazing repair process according to claim 1, characterized in that: The combined coupling agent primer is a mixture obtained by mixing 3-aminopropyltriethoxysilane and 3-mercaptopropionic acid in a volume ratio of 1.12:0.78-1.43 and stirring at room temperature for 15 minutes.
6. The ceramic crack glazing repair process according to claim 1, characterized in that: S3: the sintering temperature in the second stage is 1200-1220°C, and the heat preservation time is 180-210min; the cooling rate in the third stage is 2.5°C / min.
7. A ceramic crack repair glaze, characterized in that: The ceramic crack repair glaze used in the ceramic crack glazing repair process as claimed in claim 1 comprises a repair glaze A and a repair glaze B; In parts by weight, the raw materials of the repair glaze A are: 32 parts of halloysite, 15-18 parts of phosphotquartz, 10-13 parts of leucite, 5-8 parts of wollastonite, 6 parts of barium carbonate, 5 parts of zinc oxide, 8 parts of zirconium silicate and 15-20 parts of modified mullite; In parts by weight, the raw materials of the repair B glaze are: 32 parts of halloysite, 18 parts of phosphate quartz, 13 parts of white garnet, 5 parts of zinc oxide, 5-12 parts of medium-temperature frit, 6 parts of barium carbonate, 2-8 parts of tin oxide, 2-5 parts of titanium oxide, 20 parts of modified mullite, and 0.2-0.5 parts of polyvinyl alcohol.
8. The ceramic crack repair glaze according to claim 7, characterized in that: The raw materials of the repair glaze A and the repair glaze B are respectively put into a ball mill, and 28% water of the total mass of the raw materials of the A glaze and the B glaze is added respectively. After ball milling for 36 hours, the raw materials are sieved through a 180-mesh sieve to obtain the repair glaze A and the repair glaze B.
9. The ceramic crack repair glaze according to claim 7, characterized in that: Mullite with a particle size of 25-50 μm is soaked in a boric acid solution with a mass concentration of 8% at room temperature for 60 minutes, then filtered, washed and dried to obtain the modified mullite; the mass ratio of the mullite to the boric acid solution is 1:2.
8.
10. The ceramic crack repair glaze according to claim 7, characterized in that: In parts by weight, the raw materials of the repair glaze A are: 32 parts of halloysite, 18 parts of quartz, 13 parts of leucite, 8 parts of wollastonite, 6 parts of barium carbonate, 5 parts of zinc oxide, 8 parts of zirconium silicate and 20 parts of modified mullite.
Citation Information
Patent Citations
Repairing method for sanitary ware
CN103102174A
Recycled glaze for ceramic repair and repair method
CN106083202A
Sanitary ceramics mending material and mending method
CN106746664A
Ceramic repairing method
CN111718209A
Matt black glaze and sanitary ware and preparation method and application thereof
CN113651536A